Efficacy of dupilumab with concomitant topical calcineurin inhibitors treatment for preschool children with atopic dermatitis: a retrospective cohort study - Wu Liming; Kamran Ali (Annals of Medicine)
Background/objective Atopic dermatitis (AD) is a chronic, relapsing inflammatory skin disease that typically occurs in childhood/infancy and is associated with complications like extracutaneous atopic morbidity. Providing systemic treatment for pediatric AD patients with unmet comprehensive medical needs remains challenging. We present a cohort study describing the efficacy and safety of dupilumab combined with topical calcineurin inhibitors (TCI) in children with moderate-to-severe atopic dermatitis under the age of 6 years.Methods A retrospective cohort study was conducted at a single center to analyze the use of dupilumab in combination with topical calcineurin inhibitors (TCI) in children aged 6 years and under moderate-to-severe AD that was inadequately controlled with topical therapy.Results Overall, 23 preschool children (mean [SD] age, 4.78 [1.278] years); 10 boys (43.5%) and 13 girls (56.5%) received 300 mg dupilumab every four weeks and TCI. The primary outcome, the average Eczema Area and Severity Index (EASI) percentage reduction from baseline, was −70.85%. Significant improvement was also observed in secondary outcomes: caregiver-reported Peak Pruritus numerical rating scale (P-NRS) (−77.73%), Body Surface Area (BSA) (−62.11%), and Investigators Global Assessment (IGA) (−36.23%) at week 16. A 1–2 grade decrease in IGA after 16 weeks of treatment was achieved by 91.3% of patients. There was a significant improvement in P-NRS and EASI scores from baseline to week 16. Injection-site reaction (one patient) and facial redness (two patients) were recorded. No severe drug-related adverse events were observed.Conclusion This study demonstrated that the combination of dupilumab and TCIs improved symptoms and quality of life in preschoolers with moderate-to-severe AD.